Trichophyton as a Rare Cause of Postoperative Wound Infection Resistant to Standard Empiric Antimicrobial Therapy - Sheema Gaffar; John K. Birknes; Kenji M. Cunnion (Case Reports in Pediatrics)
Fungal infections are rare causes of acute surgical wound infections, but Candida is not an infrequent etiology in chronic wound infections. Trichophyton species is a common cause of tinea capitis but has not been reported as a cause of neurosurgical wound infection. We report a case of Trichophyton tonsurans causing a nonhealing surgical wound infection in a 14-year-old male after hemicraniectomy. His wound infection was notable for production of purulent exudate from the wound and lack of clinical improvement despite empiric treatment with multiple broad-spectrum antibiotics targeting typical bacterial causes of wound infection. Multiple wound cultures consistently grew Trichophyton fungus, and his wound infection clinically improved rapidly after starting terbinafine and discontinuing antibiotics.